2004
DOI: 10.1007/bf02931653
|View full text |Cite
|
Sign up to set email alerts
|

Chitosanase activity inBacillus thuringiensis

Abstract: The ability to produce extracellular chitosanase (EC 3.2.1.132) was found by plate assays in 18 (23%) out of 77 crystalliferous strains of Bacillus thuringiensis. The best chitosanase producer was selected after the growth chosen in a liquid medium with colloidal chitosan as carbon source. Enzyme production was optimized (a 4-d incubation at 32 degrees C with shaking in a medium of pH 6.5 with 4% colloidal chitosan) and the enzyme was partially characterized. This is the first report on the chitosanase of B. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Hence, the production of COS using glycolytic enzymes is more efficient and desirable. Accordingly, chitosanases have been isolated from bacteria (Choi et al , 2004; Cruz Camarillo et al , 2004; Yun et al , 2005; Su et al , 2006), fungi (Nogawa et al , 1998; Cheng & Li, 2000; Zhang et al , 2000) and plants (Osswald et al , 1994), with a view to using them in the production of COS.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the production of COS using glycolytic enzymes is more efficient and desirable. Accordingly, chitosanases have been isolated from bacteria (Choi et al , 2004; Cruz Camarillo et al , 2004; Yun et al , 2005; Su et al , 2006), fungi (Nogawa et al , 1998; Cheng & Li, 2000; Zhang et al , 2000) and plants (Osswald et al , 1994), with a view to using them in the production of COS.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal chitosan was prepared based on the method adopted by Cruz Camarillo et al, (2003) [4] with slight modification. Crude chitosan flake was procured from MATSYAFED, Kerala State Co-operative Federation for Fisheries Development Ltd. Neendakara, Kerala.…”
Section: Synthesis Of Colloidal Chitosanmentioning
confidence: 99%
“…The absence of bands with MW close to 70,000 indicated that most of chitosanolytic activity resides in a minority protein. The molecular mass of chitosanases from various B. thuringiensis strains is in the range between 46-59 kDa [31,32], as occurs in chitosanases from related bacterial species such as B. cereus [42] and B. megaterium [43], but higher than in other Bacillus species (20-30 kDa) [44]. In contrast, chitinases from B. thuringiensis are slightly larger (66-75 kDa) [27,45].…”
Section: Isolation and Characterization Of B Thuringiensis Chitosanolytic Activitymentioning
confidence: 99%
“…It also displays proteinase, chitinase [27][28][29] and chitosanase [30] activities, which are probably involved in its ecological interactions as well as in the insecticidal and antifungal action, and could expand its range of applications [18]. Cruz-Camarillo et al first described a chitosanase activity in various strains of B. thuringiensis [31]. Lee et al reported the isolation of several of these enzymes [32].…”
Section: Introductionmentioning
confidence: 99%